Compact gain-switched Tm:YAP laser pumped by a high power laser diode around 790 nm. (9th June 2015) - Cai, Shuangshuang; Yang, Dingzhong; Wu, Pinghui; Hu, Chengzhi; Jiang, Peipei
Abstract: We report, to the best of our knowledge, the first demonstration of stable pulse generation from a gain-switched Tm:YAP laser directly pumped with a modulated high power laser diode around 790 nm. A piece of Tm:YAP crystal (3% Tm 3+ doping) 5 mm in diameter and 12 mm in length was used as the gain medium. To realize effective gain-switching pulse operation, the laser diode was modulated with suitable pulse repetition rates and corresponding pulse durations. Stable single pulse output was achieved with repetition rates from 1 to 20 kHz. By adjusting the cavity parameters, a maximum laser output power of 4.6 W was obtained under a pump power of 16 W with corresponding overall optical-to-optical conversion efficiency of 28.7%.